THE ROLE OF CUSTOMER DUE DILIGENCE IN MITIGATION OF CREDIT FINANCING RISK IN SHARIA FINANCIAL INSTITUTIONS AT BSI PAREPARE BRANCH - widya, vira; Akilah, Fahmiah (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2025)
This study examines the implementation of Customer Due Diligence (CDD) at BSI KC Parepare, focusing on three main aspects: the quality of CDD in mitigating financing risks, customer characteristics considered in its application, and the factors determining its effectiveness. The purpose is to analyze how CDD helps the bank identify, measure, and reduce financing risks from the early stages and to evaluate its effectiveness in preventing problematic financing. This research employs a qualitative method with a case study approach, using interviews, field observations, and documentation related to financing policies and the implementation of the Know Your Customer (KYC) principle. The findings show that CDD plays a crucial role in risk mitigation, particularly in assessing customer eligibility, analyzing business backgrounds, and monitoring transactions. This role has been proven to reduce potential financing risks and improve the quality of the bank’s financing portfolio.